2018
DOI: 10.1647/2017-261
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Clinical Signs and Gross Pathologic Findings in Birds Infected WithMycobacterium genavense

Abstract: Mycobacterium genavense is regarded as the primary cause of mycobacteriosis in passerine and psittacine birds kept in captivity. Mycobacterium genavense is a potential zoonotic pathogen; therefore, early antemortem detection in birds is needed. In humans, infections with M genavense are found predominantly in immunocompromised people. To investigate clinical signs and pathologic lesions and to determine the prevalence of coinfections in birds infected with M genavense, we reviewed records of 83 birds in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Mycobacteriosis in the examined canaries may have been promoted by immunosuppression caused by the concurrent CaCV and CaPyV infections, as it also may have been by FPyV infection in the Bengalese finch. In a retrospective study conducted by Schmitz et al (31) in birds with mycobacteriosis caused by M. genavense detected post mortem, polyomavirus infection was revealed in 25% and circovirus infection in 35% of cases. However, the birds most susceptible to mycobacteriosis were those infected with both of these viruses.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Mycobacteriosis in the examined canaries may have been promoted by immunosuppression caused by the concurrent CaCV and CaPyV infections, as it also may have been by FPyV infection in the Bengalese finch. In a retrospective study conducted by Schmitz et al (31) in birds with mycobacteriosis caused by M. genavense detected post mortem, polyomavirus infection was revealed in 25% and circovirus infection in 35% of cases. However, the birds most susceptible to mycobacteriosis were those infected with both of these viruses.…”
Section: Discussionmentioning
confidence: 96%
“…Due to the concurrent CaCV and CaPyV infections in canary 4, it is difficult to determine which virus had a greater effect on the loss of feathers on the tail. Schmitz et al (31) suggested a significant effect of polyomavirus on moulting in birds. Typical changes in the blood counts associated with mycobacteriosis are leukocytosis, significant heterophilia and monocytosis (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grey parrots are the only birds in which cases of tuberculosis caused by M. tuberculosis and M. bovis are often detected (Schmidt et al, 2008;Washko et al, 1998;Fulton and Sanchez, 2013). The reason for the high prevalence of mycobacterial infections among parrots, especially caused by M. genavense, may be genetic factors, specific susceptibility of species, as well as exogenous causes (housing conditions, congestion, stress, etc.…”
mentioning
confidence: 99%
“…silvaticum, Mycoplasma sp., Salmonella sp., Escherichia coli, Aspergillus sp., etc. ), violating the immune status, promote the activation of M. genavense in the host (Schmitz et al, 2018a(Schmitz et al, , 2018bManarolla et al, 2007). www.jvmbbs.kharkov.ua Diagnosis of mycobacteriosis caused by M. genavense is based on the detection of acid-fast rods stained by the method of Ziehl-Neelsen in combination with the culture method on special media for 6-12 weeks (Realini et al, 1999).…”
mentioning
confidence: 99%